The Creative Neurons - Flinn, Mark V. (Frontiers in Psychology, 2021)
Creativity generates novel solutions to tasks by processing information. Imagination and mental representations are part of the creative process; we can mull over ideas of our own making, and construct algorithms or scenarios from them. Social scenario-building can be viewed as a human cognitive ‘super-power’ that involves abstraction, meta-representation, time-travel, and directed imaginative thought. We humans have a ‘theater in our minds’ to play out a near-infinite array of social strategies and contingencies. Here we propose an integrative model (Tinbergen, 1963) for why and how humans evolved extraordinary creative abilities. We posit that a key aspect of hominin evolution involved relatively open and fluid social relationships among communities, enabled by a unique extended family structure similar to that of contemporary hunter-gatherer band societies (Walker et al, 2011). Intercommunity relationships facilitated the rapid flow of information – “Culture” – that underpinned arms-races in information processing, language, imagination, and creativity that distinguishes humans from other species.